Odpowiedzi

Najlepsza Odpowiedź!
2010-01-24T19:31:22+01:00
A) a(a+b+c)-b(a-b+c)-c(a-b-c)=
a²+ab+ac-ab+b²-bc-ac+bc+c² =
= a² +b² + c²

b)x(x²+2x+1)-(-4x³+8x²-6):2=
x³+2x²+x-(-2x³+4x²-3)=
= x³+2x²+x+2x³-4x²+3 =
= 3x³-2x²+x+3
2010-01-24T19:36:05+01:00
A)a²+ab+ac-ab+b²+bc-ac+bc+c²=a²+b²+c²
b)1/2(x³+2x²+1x-4x³-8x²+6)=1/2(-3x³-6x²+x)=-1,5x³-3x²+1/2x
2010-01-24T20:10:18+01:00
A) a(a+b+c)-b(a-b+c)-c(a-b-c) =a² + ab + ac - ab + b² - bc - ac + bc + c² = a² + b² + c²
b)x(x²+2x+1)-(-4x³+8x²-6):2 = x³ + 2x² + x + 2x³ - 4x² + 3 = 3x³ - 2x² + x + 3